2015
DOI: 10.1159/000431322
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Psychological Profile of Patients with Laryngopharyngeal Reflux

Abstract: Background/Aims: Psychological factors have been claimed to play a role in the predisposition for laryngopharyngeal reflux (LPR) symptoms. The aims of this work were to study the relationship between psychological disorders and LPR and to investigate the effect of potential psychological disorders on patients' self-perception of reflux-related problems. Methods: Forty-two patients with symptoms suggestive of LPR were psychologically evaluated using the Social Readjustment Rating Scale, the Symptom Checklist-90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…The sensation of sticking in the throat can appear continuously so that it can cause psychological disorders. [15][16][17] The results showed that there was no significant association between risk factors as gender, age, duration of symptoms, BMI, smoking and diet with psychiatric symptoms: depression, anxiety and stress. In another study also reported that there was no relationship between gender, age, BMI, and smoking habits and the patient's quality of life for LPR.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The sensation of sticking in the throat can appear continuously so that it can cause psychological disorders. [15][16][17] The results showed that there was no significant association between risk factors as gender, age, duration of symptoms, BMI, smoking and diet with psychiatric symptoms: depression, anxiety and stress. In another study also reported that there was no relationship between gender, age, BMI, and smoking habits and the patient's quality of life for LPR.…”
Section: Discussionmentioning
confidence: 90%
“…It can be caused LPR symptoms resemble symptoms of serious diseases such as cancer making the concerns of patients to seek immediate treatment so that the disease does not develop further into keganasan. 7,15 Severe symptoms of LPR such as pharyngeal globus, persistent psychogenic cough, hoarseness and dysphagia can be a cause of stress, anxiety and depression. Symptoms of LPR such as hoarseness and the sensation of a foreign body in the throat can trigger patient anxiety because of his concern for a sign of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, in other studies, patients with LPR did not demonstrate any psychological distress 2728. Mesallam et al28 reported that the psychological background of patients with LPR does not affect the patients' self-perception of their reflux-related problem. Chronic laryngeal signs and symptoms associated with gastroesophageal reflux (GERD) are often referred to as LPR or reflux laryngitis.…”
Section: Discussionmentioning
confidence: 91%
“…A recent cohort study found that one-third of patients with LPR suffer from anxiety and significantly reduced social activities compared with those in controls 26. However, in other studies, patients with LPR did not demonstrate any psychological distress 2728. Mesallam et al28 reported that the psychological background of patients with LPR does not affect the patients' self-perception of their reflux-related problem.…”
Section: Discussionmentioning
confidence: 96%
“…We hypothesized that this was related to personal psychological characteristics: low self-esteem was associated with a high level of anxiety, stress and depression [ 35 ]. The association between psychological characteristics and LPR is controversial with only a few researchers discussing this issue [ 7 , 36 , 37 ]. In our previous study, we observed depressive symptoms to be positively associated with LPR symptoms [ 7 ].…”
Section: Discussionmentioning
confidence: 99%